Facilitating Cross-Border Trade between the DRC and Neighbors in the Great Lakes Region of Africa : Improving Conditions for Poor Traders - World Bank (World Bank, 2012)
This report looks at the current situation and opportunities for cross-border trade between Democratic Republic of Congo (DRC) and neighbors with a focus on agricultural products. It recognizes that much of current trade across these borders is informal and carried by individual traders, most of whom are poor women. The report shows that it is very important that informality not be equated with illegality. The large numbers of traders that cross the border every day do so through official border crossings. The aim of the report is to provide information on the current state and the potential for cross border trade between the DRC and Burundi, Rwanda and Uganda, to document the conditions and problems that traders face in crossing the borders and provide suggestions to policy makers on the priorities for trade facilitating measures at the border. Exploiting the potential for cross-border trade will be an important element of growth and poverty reduction in the region and a key mechanism for enhancing stability. Comparing prices for food products in a range of markets in the three countries, the report underlines the strong role that cross-border trade could play in reducing differences in price levels and price volatility of agricultural products. The report proceeds by describing the current economic situation in the Great Lakes region and then provides a brief summary of a detailed analysis of relative prices of a number of basic food products in markets in Burundi, DRC and Rwanda and what this implies for the width of the borders in the region. The next section then summarizes the results from the survey of cross-border traders which is followed by a set of recommendations. The final section concludes and describes a number of steps that are being taken to address the constraints identified in this report and discusses ways in which these may be built upon.